Scaling up Kudumbashree -- collective action for poverty alleviation and women's empowerment - Kadiyala, Suneetha (International Food Policy Research Institute, 2004)
This paper discusses the factors that enabled and constrained the scaling up of a multisectoral poverty alleviation program called Kudumbashree, initiated by the government of Kerala (GOK), India, in 1998 to eradicate poverty by 2008. It also discusses some potential threats to and trade-offs of scaling up Kudumbashree. This report draws primarily upon the available literature and qualitative data collected during a five-day visit to Kudumbashree in March 2003....Our findings show that an enabling environment, especially decentralization and the concurrent devolution of finances to the local government bodies (LGBs), was critical in scaling up Kudumbashree. The CDS structures are now considered as a further step to decentralization. As the CDS structures are affiliated to the LGBs, their financial sustainability is ensured through various modalities, e.g., convergence, women's component plan, and earmarked assistance to women's self-help groups (SHG). The unique context of Kerala, coupled with leadership of a few motivated and innovative officials, was key in both the decentralization and scaling-up process.